Internal audit quality, punitive measures and accountability in Ugandan statutory corporations - Nalukenge, Irene; Kigongo Kaawaase, Twaha; Bananuka, Juma; Ogwal, Peter F. (Journal of Economic and Administrative Sciences, 2021)
This study aims to (1) examine the contribution of internal audit quality, punitive measures to accountability in statutory corporations in developing countries such as Uganda and (2) test whether internal audit quality mediates the relationship between punitive measures and accountability in Uganda’s statutory corporations. Design/methodology/approach – This study is cross-sectional and correlational. Data were collected through a questionnaire survey conducted for 82 statutory corporations. The study’s unit of analysis was a statutory corporation. Chief Internal Auditors and Chief Finance Officers were the study’s unit of inquiry. Data were analyzed through correlation coefficients and linear regression using Statistical Package for Social Sciences. Findings – The results suggest that internal audit quality and punitive measures independently predict accountability. However, punitive measures do not predict accountability in the presence of internal audit quality. Results further indicate that internal audit quality mediates the relationship between punitive measures and accountability in Uganda’s statutory corporations. Originality/value – This study confirms internal audit quality (a preventive measure) as a significant predictor of accountability in statutory corporations relative to punitive measures. To achieve accountability, more emphasis thus needs to be put on preventive mechanisms than on punitive mechanisms. This study also enhances our understanding of the relationship between punitive measures, internal audit quality and accountability. In this study, we arrive at new evidence on the mediating role of internal audit quality in the relationship between punitive measures and accountability in Uganda’s statutory corporations.
Keywords: Accountability; Punitive measures; Internal audit quality; Statutory corporation; Uganda